The Effect of Snakes and Ladders Game on Students’ Science Literacy on Solar System Materials in Elementary School - Siti Soleha; Reza Ariefka (Research, Training and Philanthropy Institution Natural Aceh, 2026)
The results of the 2022 PISA show a decline in Indonesian students' scientific literacy, necessitating innovation in learning media. This study aims to examine the effect of the Snakes and Ladders game on the scientific literacy of sixth-grade students at SDN 01 Tuguharum on the solar system. The Snakes and Ladders game was chosen because its visual, interactive, and rule-based nature is suitable for scientific concepts. The method used was quantitative with a Nonequivalent Control Group design. The sample consisted of 44 sixth-grade students divided into experimental and control groups. Data were collected through tests and documentation, then analyzed using instrument testing and hypothesis testing. The results showed that students in the experimental group scored higher than those in the control group (t = 11.99, p < 0.05), indicating that the Snakes and Ladders game media had a positive effect on students' scientific literacy. This finding contributes to improving students' ability to explain scientific phenomena. The implication is that Snakes and Ladders can serve as a practical and engaging alternative to science education in elementary schools.